(untitled) (Revista Apotheke, 2020)
The article approaches the educational proposals and activities carried out in the exhibition “Ephemerality and Persistence”, whose theme was launched in the discipline “Educational Action in Cultural Institutions”, from the Postgraduate Program in Visual Arts (PPGAV) of the University of the State of Santa Catarina (UDESC). The contemporary art project carried out the “Aesthetic Space” of the Colégio de Aplicação of the Federal University of Santa Catarina (UFSC) in Florianópolis/SC, Brazil, in 2018, which integrated alumni who are teachers/ educators from universities, institutes, schools and cultural institutions. It revealed challenges due to two factors: development of an exhibition proposal in a formal education school, linked to a cultural mediation for a specific audience.